High density lipoprotein (HDL)-associated sphingosine 1-phosphate (S1P) inhibits macrophage apoptosis by stimulating STAT3 activity and survivin expression. (February 2017) - Feuerborn, Renata; Becker, Susen; Potì, Francesco; Nagel, Petra; Brodde, Martin; Schmidt, Harmut; Christoffersen, Christina; Ceglarek, Uta; Burkhardt, Ralph; Nofer, Jerzy-Roch
Abstract: Background and aims: Macrophage apoptosis is critically involved in atherosclerosis. We here examined the effect of anti-atherogenic high density lipoprotein (HDL) and its component sphingosine-1-phosphate (S1P) on apoptosis in RAW264.7 murine macrophages. Methods: Mitochondrial or endoplasmic reticulum-dependent apoptosis was induced by exposure of macrophages to etoposide or thapsigargin/fukoidan, respectively. Results: Cell death induced by these compounds was inhibited by S1P as inferred from reduced annexin V binding, TUNEL staining, and caspase 3, 9 and 12 activities. S1P induced expression of the inhibitor of apoptosis protein (IAP) family proteins cIAP1, cIAP2 and survivin, but only the inhibitor of survivin expression YM155 and not the cIAP1/2 blocker GDC0152 reversed the inhibitory effect of S1P on apoptosis. Moreover, S1P activated signal transducer and activator of transcription 3 (STAT3) and Janus kinase 2 (JAK2) and the stimulatory effect of S1P on survivin expression and inhibitory effects on apoptosis were attenuated by STAT3 or JAK2 inhibitors, S3I-201 or AG490, respectively. The effects of S1P on STAT3 activation, survivin expression and macrophage apoptosis were emulated by HDL, HDL lipids, and apolipoprotein (apo) M-containing HDL, but not by apoA-I or HDL deprived of S1P or apoM. In addition, JTE013 and CAY10444, S1P receptor 2 and 3 antagonists, respectively, compromised the S1P and HDL capacities to stimulate STAT3 activation and survivin expression, and to inhibit apoptosis. Conclusions: HDL-associated S1P inhibits macrophage apoptosis by stimulating STAT3 activity and survivin expression. The suppression of macrophage apoptosis may represent a novel mechanism utilized by HDL to exert its anti-atherogenic effects. Graphical abstract: Highlights: S1P inhibits mitochondrial and endoplasmic reticulum-dependent apoptosis in macrophages. Inhibitory effects of S1P on apoptosis depend on the increased expression of survivin. Survivin upregulation by S1P is mediated through activation of JAK2 and STAT3. High density lipoprotein emulates anti-apoptotic effect of S1P in macrophages.